2016
DOI: 10.4236/ampc.2016.67017
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation Kinetics and Breaking of a Thin Water Liquid Bridge between Two Plates of Silicon Wafer

Abstract: In ceramic processing, the study of the different phases of the drying stage considers the material at a macroscopic scale. Very often, the various parameters (among which the temperature and the relative humidity) are chosen in an empirical way, mostly through visual observations. This stage is governed by capillary phenomena which take place within the material, responsible for both the shrinkage and the risk of cracks which can damage the final piece. As part of a better understanding of the local mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
(16 reference statements)
2
13
0
Order By: Relevance
“…We encourage the interested reader to find more details about the specific device used in this study in our previous work [11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We encourage the interested reader to find more details about the specific device used in this study in our previous work [11].…”
Section: Methodsmentioning
confidence: 99%
“…These measurements consist in a three steps procedure. First, liquid bridges with an initial volume of 4.0 μL ± 0.1 μL were produced and observed during drying (varying the initial volume is investigated in our previous work in the case of hydrophilic contacts [11]). The dimensions are given in Figure 5…”
Section: Liquid Bridge Volume and Area Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear m versus t relationship, meaning a constant evaporation rate, has also been observed in previous experiments carried out under conditions similar to the setup reported here, though addressed to investigate liquid bridge instabilities and the capillary force between surfaces. [24][25][26] Of course, our straightforward model is expected to depart from experimental data when the thinned liquid bridge finally breaks up, and hence Equation 4should not be extrapolated to the final period of drop evaporation. Still, the slope of the curve on the first stages of evaporation appropriately represents the kinetics, and it will be the object of analysis hereafter.…”
Section: The Evaporation Kinetics Of Confined Dropletsmentioning
confidence: 99%
“…This argument is also supported by a previous experimental investigation that measured the evaporation rate of droplets squeezed between parallel plates under different RH conditions. [25] These authors found that, for a 4 mL droplet placed between (noncoated) silicon wafers with a gap of 0.5 mm, the evaporation time was duplicated, whereas RH ambient condition was increased from 35% to 75%. It is worth to remember that, in our experiments with N-W surfaces, the RH increase is not externally controlled but self-generated around the peripheries of the squeezed drop.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%